Somatic mutations, acetylator status, and prognosis in colorectal cancer. Issue 5 (1st May 1998) - Hardingham, J E; Butler, W J; Roder, D; Dobrovic, A; Dymock, R B; Sage, R E; Roberts-Thomson, I C
Abstract : Background— Somatic mutations in K- ras and TP53 may be associated with both acetylator status and prognosis in colorectal cancer. Aims— To determine whether cancers with somatic mutations are more frequent in fast acetylators and whether mutations or acetylator status influence prognosis after colorectal surgery. Patients— One hundred consecutive subjects undergoing elective surgery for colorectal cancer. Methods— Acetylator status was determined by polymerase chain reaction (PCR) genotyping for polymorphism in the N-acetyltransferase 2 ( NAT 2) gene. Mutations in K- ras (codon 12) and TP53 were determined by PCR analysis using restriction enzyme digestion and single strand conformation polymorphism respectively. Survival from colorectal cancer for up to five years after diagnosis was analysed using the Kaplan-Meier product limit estimator. Cox proportional hazards regression was used to compare survival rates after adjusting for tumour stage. Results— Mutations in K- ras and TP53 were independent of acetylator status. By log rank test, survival was significantly reduced in subjects with TP53 mutations (p=0.003) but was not significantly related to acetylator status or the presence of K- ras mutations. After adjustment for tumour stage, subjects with both TP53 and K- ras mutations had a 4.2-fold case fatality (95% confidence interval 1.5 to 11.6) when compared with that of a TP53 negative reference group. Conclusion— The presence of both TP53 and K- ras mutations in colorectal tumours is an adverse prognostic marker which is independent of tumour stage.